Analisis Kapasitas Vo2 Max Siswa Kelas Xi Di SMA Negeri 5 Manna Bengkulu Selatan - Lovenza, Olyvia; Asnawati, Asnawati; Martiani, Martiani (Journal Of Dehasen Educational Review, 2024)
This research aims to see the VO2 Max capacity of class XI students at SMA Negeri 5 Manna South Bengkulu. The research method used is quantitative method. The research instrument used in this study was the multistage-20 m-shuttle run test. The sample in the study were male students in class XI IPA 1, totalling 10 people. The results of this study are VO2 Max capacity of class XI students at SMA Negeri 5 Manna, South Bengkulu Regency is included in the sufficient category with a value of 8.2. Of the 10 research samples, there were 0 testers in the Very Good category, 1 tester in the Very Good category, 2 testers in the Good category, 4 testers in the Fair category, 3 testers in the Less category, and 0 testers in the Very Less category. Based on the measurement results, the highest value is 11 with a very good category while the lowest measurement result is 6 with a less category.